The chemical compositions of Rhododendron arboreum, “Laligunras” - Shrestha, Roshani M.; Budhathoki, Narendra pratapsingh (Journal of Nepal Chemical Society, 2013)
Rhododendron arboreum, family Ericaceae, is a medium size tree 7-14m height or shrub, Widely distributed in Nepal all along sub-tropical and temperate regions from 1200-3300m, the Rhododendron arboreum is known as ‘Gunras’ in Nepali. R. arboreum was declared of Nepal’s national flower in 1962 by government of Nepal. The chemical compositions of the wood (stem) Of Rhododendron arboreum has been investigated on the basis of useful methods of Tappi & ASTM. The main chemical compositions were:-Ash content (0.75%), Extractives (4.39%), Hollocelluloses (69.82%), Hemicelluloses (22%), alpha-celluloses (47.98%), Pentosans (16.84%), & Lignins (24.88%). The Lignins were analyzed by UV &IR. Similarly, the fatty acid compositions of extractives were analyzed by GC/MS. The main fatty acid compositions were: Butanoic acid, Pentanoic acid, 4-Heptenoic acid, & 8-Nonynoic acid in extractives. The solubility of wood in various solvents is a measure of extraneous components content. The solubility of different solvents were: - in cold water (7.02%), Hot water (8.47%), & 1% NaOH (19%). The high percentage of alpha celluloses in chemical compositions shows prospective use as a raw material for paper production along with Danphebholua (Lokta) in cottage industries of Nepal. DOI: http://dx.doi.org/10.3126/jncs.v30i0.9376 Journal of Nepal Chemical Society Vol. 30, 2012 Page: 97-106 Uploaded date: 12/19/2013